Percepção de mulheres sobre o processo saúde-doença e a assistência recebida em unidade de atenção primária à saúde de Mossoró/RN - Moura, Dávinna Nyara Lima (Universidade Federal Rural do Semi-Árido, 2020)
Understanding the social representations of the health of a given population is crucial in the development of public health policies. In this context, the individual's perception of his health status and the social determinants that act in this process are inserted. In addition, the female gender perspective brings specificities regarding access, types of services, among others. It addresses the objective of: Analyzing the understanding and health behaviors of women assisted by a Basic Health Unit (UBS). It is a study of qualitative approach, carried out in the Basic Health Unit Antônio Camilo, in which the data collection was carried out from September / 2019 to November / 2019, with the participation of 13 women who had registration in the referred health service, aged between 20 and 80 years, through audio-recorded interviews. After transcription, the data were submitted to thematic content analysis. To maintain anonymity of the participants, we identified the statements by the letter "M" followed by an Arabic number. With the analysis of the data, we obtained four categories: Dimensions of the health-disease process (related to the women's interpretation of the health status); Modes of self-care and self-care (related to disease prevention and health-seeking practices; how they were acquired); Social representations of social determinants of health (related to the perception of the influence of income and place of residence on health); Health service from the perspective of women (related to apprehension about the reality of care in the UBS). We observed that health is still related to the absence of disease. In addition, self-care dominates rather than self-care, since practices are transmitted hierarchically and without criticism. The place of residence is rarely seen as a social determinant of health. In general, the care provided by UBS is approved by the participants.
Keywords: Representação social; Saúde da mulher; Determinantes sociais em saúde; Atenção primária a saúde.; CIENCIAS DA SAUDE::MEDICINA